Media and human rights: A study of the Kashmir conflict in the Indian press - SHAHZAD, FARRUKH; Qazi, Tehmina Ashfaq; GHUMMAN, UMER SHABBER (Journal of Peace, Development and Communication, 2021)
Abstract This study examines how the Indian press reported the Kashmir conflict according to the Human Right Journalism model. We applied frame analysis on the 392 news stories of two Indian newspapers, The Hindu and Hindustan Times. The results of the study show that Indian press gave more weight to human-wrong journalism frame while reporting the happenings in Kashmir. The findings also show that the Indian press followed the national narrative and reported the events from distance frames. In terms of soft topics, the newspapers reported human-right journalism frames, but in case of hard topics, human-wrong journalism frames were applied. Limitations of the study are given at the end. Keywords: Kashmir conflict, Human rights violation, Article 370A, siege, Protest, Pellet guns.